Investigation of vibration's effect on driver in optimal motion cueing algorithm. - Hazoor Ahmad; Muhammad Tariq; Awais Yasin; Sohail Razzaq; Muhammad Ahmad Chaudhry; Inam Ul Hasan Shaikh; Ahsan Ali; Saeed Mian Qaisar; Jamshed Iqbal (PLoS ONE, 2023)
The increased sensation error between the surroundings and the driver is a major problem in driving simulators, resulting in unrealistic motion cues. Intelligent control schemes have to be developed to provide realistic motion cues to the driver. The driver's body model incorporates the effects of vibrations on the driver's health, comfort, perception, and motion sickness, and most of the current research on motion cueing has not considered these factors. This article proposes a novel optimal motion cueing algorithm that utilizes the driver's body model in conjunction with the driver's perception model to minimize the sensation error. Moreover, this article employs H∞ control in place of the linear quadratic regulator to optimize the quadratic cost function of sensation error. As compared to state of the art, we achieve decreased sensation error in terms of small root-mean-square difference (70%, 61%, and 84% decrease in case of longitudinal acceleration, lateral acceleration, and yaw velocity, respectively) and improved coefficient of cross-correlation (3% and 1% increase in case of longitudinal and lateral acceleration, respectively).